Peran Lembaga Keuangan Syariah dalam Membantu UMKM di Indonesia - Febriyani Lut’fiyah; Alya Putri Nazla; Muhammad Yusup; Aziz Muhamad Fauzi; Nurul Azmi Sibtiani; Irpan Maulana (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an essential pillar of the Indonesian economy, contributing significantly to employment creation, poverty reduction, and income distribution. However, despite their substantial role, MSMEs continue to face a number of persistent challenges, including limited access to capital, low levels of financial literacy, and inadequate utilization of technology. These barriers hinder their ability to grow, compete, and adapt to rapid economic changes. This study aims to explore and analyze the role of Islamic Financial Institutions (IFIs) in empowering MSMEs within the framework of Sharia principles. Employing a descriptive qualitative approach, this research is based on a comprehensive literature review of scholarly articles, official reports, and other relevant academic sources. The findings reveal that IFIs provide both financial and social contributions to MSMEs. Financially, IFIs channel funds through Sharia-compliant contracts such as mudharabah and murabahah, which allow entrepreneurs to access financing without relying on conventional interest-based systems. Socially, IFIs carry out a redistributive role by managing and disbursing zakat, infaq, sadaqah, and waqf (ZISWAF), while also offering entrepreneurship training, mentoring, and technical assistance. These functions collectively enhance MSMEs’ access to capital, strengthen their managerial and operational capacities, and increase competitiveness in both domestic and global markets. Nevertheless, several challenges remain, including the uneven geographical distribution of IFI services, slow adoption of digital technology, and the need for more supportive regulatory frameworks. Strengthening IFIs’ role through policy integration, technological innovation, and collaboration with government and private sectors is essential for maximizing their impact on MSME empowerment. Thus, IFIs not only act as financial intermediaries but also as socio-economic catalysts that support sustainable and inclusive economic development in Indonesia.